Improving in situ liquid SEM imaging of particles. (2nd September 2019) - Yu, Xiao‐Ying; Arey, Bruce; Chatterjee, Sayandev; Chun, Jaehun
Abstract : This work presents in situ imaging of synthesized boehmite (γ‐AlOOH) particles ranging from 20 to 100 nm, suspended in liquid, in a vacuum compatible microfluidic sample holder using a scanning electron microscopy (SEM) under the high vacuum mode and highlights the advantage of in situ liquid imaging of colloids. Nanometer‐sized boehmite particles in high‐level radioactive wastes at the Hanford site are known to be difficult to dissolve and cause rheological problems for processing in the nuclear waste treatment plant. Therefore, it is important to characterize boehmite particles and understand how they form aggregates in the liquid state. Several technical advancements are made to optimize in situ liquid SEM chemical imaging resulting in the improved ability to obtain secondary electron (SE), backscattered electron (BSE) images, and energy dispersive X‐ray spectroscopy (EDX) spectra. Moreover, our results show mixed particles could be studied and identified based on the particle shape and elemental composition using in situ SEM imaging and EDX. Thus, we provide a new and improved approach to observe the evolution of particle dispersion and stability in liquid under conditions similar to those in the waste tank.